Peningkatan Kemampuan Berpikir Kritis Siswa melalui Pendekatan Realistic Mathematics Education pada Materi Geometri dalam Pembelajaran Matematika: Studi Litertur - Sofyani Dinillah; Hasanuddin Hasanuddin (CV. Lentera Literasi Indonesia, 2026)
This study aims to examine the improvement of students’ critical thinking skills through the Realistic Mathematics Education (RME) approach in geometry topics within mathematics learning. The method employed is a literature review by examining various relevant scholarly articles obtained from the Google Scholar database. The data were analyzed using content analysis techniques through the stages of identification, classification, analysis, synthesis, and conclusion drawing. The findings indicate that the RME approach is effective in improving students’ critical thinking skills because it enables mathematical concepts to be connected with real-life contexts. In addition, the implementation of RME encourages active student participation, enhances conceptual understanding, and improves students’ ability to solve mathematical problems. Therefore, the RME approach can serve as an innovative and contextual alternative for improving the quality of mathematics learning, particularly in geometry.